PREVALENCE AND TYPES OF FALL-RELATED INJURIES AMONG UNDER FIVE CHILDREN IN IBADAN NORTH LOCAL GOVERNMENT AREA, NIGERIA NIGERIA (2012)
Globally, falls and ensuing injuries are significant causes of morbidity and mortality among under-five children. However, the associated burden and types of falls and fall-related injuries have not been adequately researched in Nigeria. This study was conducted to assess Primary Caregivers’ (PCs) level of knowledge, prevalence and types of fall-related injuries among under-five children in Ibadan North Local Government Area (IbNLGA). In this cross-sectional study, a three-stage random sampling technique was used to select 507 PCs of under-five children from five of the 12 wards within IbNLGA. A validated questionnaire which included a 30-point knowledge scale (causes of falls among under five children -9 points, prevention of falls -18 points and outcome of falls -3 points) was used for data collection from selected caregivers. Information was also obtained on the occurrence and outcome of falls sustained by each caregivers’ youngest under-five child (index child). Respondent’s scores were categorized as good (21-30 points), average (11-20 points) and poor (0-10 points). Data were analyzed using descriptive statistics and Chi-square. The PCs consisted predominantly of biological mothers (91.0%). Their mean age was 32.3±8.1 years and a larger proportion of them (43.8%) were secondary school certificate holders. Respondents’ median number of children was one (range 1 – 3) and 54% of the children were males. Of the children, 47% sustained at least a fall in a rented apartment (65.9) with majority having chair fall (25.8). Of this, 56.4% sustained injuries that required first aid interventions and 51.7% were admitted in a hospital for a median period of three days (range 1 – 9). Injuries sustained included bruises and minor swellings (63.2%), abrasions (33.8%) and fractures/dislocation (1.5%). Most of the PCs (85.6%) had good knowledge of falls and their mean knowledge score was 23.9±3.1. All the respondents mentioned at least one strategy for preventing falls. Strategies adopted included close supervision (82.8%), cautioning (59.2%), good housekeeping practices (7.7%) and environmental modifications (3.2%). More children of PCs aged ≤20 years (61.0%) were found to have sustained a fall compared with those aged ≥41 years (15.4%), (p < 0.05). A higher proportion of children of PCs who were Yoruba (51.9%) sustained a fall than the PCs who were Hausa (40.6%) and Igbo (35.5%) (p < 0.05). A higher proportion of children aged 12-24 months (61.2%) experienced falls compared with those aged <12months (39.7%), 37-48 months (34.5%) and 49-59months (33.0%) (p<0.05). Prevalence of fall-related injuries among the under-five children poses a serious challenge of public health importance. This is because under-five is a period to determine their potential to learn and thrive for a life time, their physical and intellectual development might be impaired. Knowledge of prevention of falls was high but only a few were aware of appropriate preventive measures. Interventions to increase knowledge of primary caregivers are therefore recommended.